GERAKAN MAHASISWA DI INDONESIA DALAM BINGKAI KEKUASAAN ORDE BARU (1966-1998) - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2014)
This study discusses the dynamics of Indonesian student movement in the New Order era between 1966 until 1998. It also analyses the responses of the authority to their movement and its impact. This research uses the qualitative method of literature review and interviews where the arguments are presented in descriptive analysis. Based on Antonio Gramsci’s concept of hegemony, this study has uncovered the hegemonic means utilized by the authority to undermine student movement. The description of how this social formation was defragmented, justified and then integrated into bureaucratic processes where their existence was then consented as a subordinated class. In reality, the student movement under the New Order government was closely related to the situation of socio-politics and character of the regime. Nevertheless, the Asian economic crisis jolted the revival of the student movement to its initial vibrant state which brought down Suharto’s regime in 1998. This study has proven that hegemonic process also has a shelf-life as the masses will eventually see through the regime’s political construction. This eventuality was due to external and internal factors such as development of information technology, the rise of cyber-power, international politics and the emergence of new ideas.